Lifetime parenthood in the context of single- and multiple-partner fertility. (March 2021) - Andersson, Linus
Highlights: High total number of years as parent to dependent offspring is an important but rarely studied correlate of multi-partner fertility. We estimate that 25% of women who have children with more than one partner spend 20 or more years as co-residing, biological parent to a child no older than 18 without co-residing with the biological father of that child. 75 % of male men who have children with more than one partner spend 31 years or more years as biological parent to a offspring no older than 18. Abstract: The proportion of life spent caring for dependent children is a defining feature of life courses. This study uses Swedish register data to analyze the period of life spent as parents to children no older than 18 as a salient difference between single- and multiple-partner fertility trajectories. Individuals who have children with more than one partner spend a much longer time as parents to dependent children than those who have children with one partner, on average 8.2 more years among men and 6.2 more years among women. Cross-partner birth spacing is a more powerful proximate cause of this gap than completed fertility. We argue that an extended time parenthood is part and parcel to multi-partner fertility and discuss implications of this.